Empirical Relevance of the Hillman Condition and Comparative Advantage - Jeroen Hinloopen; Charles van Marrewijk (Tinbergen Institute, 2004)
We analyze the empirical violation of the Hillman condition, a necessary and sufficient condition for the correspondence between comparative advantage and pre-trade relative prices. Our comprehensive data set allows us to investigate the Hillman condition for virtually all countries of the world, over an extended period of time, for many sectors, and for different levels of aggregation. Violations of the Hillman condition are small as a share of the number of observations, but can be substantial as a share of the value of world exports. Measured either way, violations occurred much more frequently in the 1970s and early 1980s, a difference mostly caused by the two oil crises. As the condition is useful for identifying various anomalies, we argue that it should be included as a standard diagnostic test for empirical studies into comparative advantage.
Keywords: C81; D43; F11; F20; 330; Balassa index; Hillman condition; comparative advantage; Komparativer Vorteil; Relativer Preis; Schätzung; Welt